Capital Structure and Speed of Adjustment in Indonesian Listed Firms: Does Sharia Compliance Affect the Adjustment Speed? - Bandawaty, Euis; Anglia Banda Sutomo, Woro; Herawati, Heny; Lestari, Sri; Juliana,; Halim, Mohd; Hendayana, Yayan (Journal of Islamic Economics and Business, 2025)
This study investigates how Sharia compliance and Islamic debt constraints influence capital structure and its adjustment speed among non-financial firms listed on the Indonesia Stock Exchange (2013–2023). Challenging the assumption that Sharia-compliant firms are always more conservative in debt usage, this research integrates Sharia-based variables into a dynamic Partial Adjustment Model (PAM) using the Generalized Method of Moments (GMM). The model incorporates target leverage, adjustment speed, and Sharia principles through compliance status and debt-to-equity ratio (DER) thresholds. Empirical results reveal that Sharia-compliant firms, while maintaining DER within the 45% limit, tend to use more debt and adjust faster toward target leverage. These findings suggest that Sharia norms enhance rather than constrain financial efficiency. The study underscores the strategic role of sukuk and values-based financing in promoting disciplined and adaptive capital structures, with key implications for regulators, firms, and investors.